Water and Nitrogen Management at the Booting Stage Affects Yield, Grain Quality, Nutrient Uptake, and Use Efficiency of Fragrant Rice Under the Agro-Climatic Conditions of South China - Deng, Siying; Ashraf, Umair; Nawaz, Mohsin; Abbas, Ghulam; Tang, Xiangru; Mo, Zhaowen (Frontiers in Plant Science, 2022)
The present study was conducted to assess the effects of water and nitrogen applications at the booting stage on yield, grain quality, and nutrient use efficiencies in fragrant rice in the early (March-July) and late (July-November) seasons in 2013. The experiment was comprised of two fragrant rice cultivars i.e., Nongxiang 18 and Basmati; three nitrogen levels i.e., 0 kg N ha-1 (N0), 30 kg N ha-1 (N1), and 60 kg N ha-1 (N2) and three water levels i.e., 2-4cm water layer well-watered (W0), soil water potential was ‒15±5 kPa (W1), and soil water potential was ‒25± 5kPa (W2), which were randomized in a split-split plot design. Results showed that Basmati produced higher grain yield than Nongxiang 18 (16.20% and 9.61% in early and late season, respectively), whereas the W1 had the maximum grain yield and harvest index. The moderate application of nitrogen (N1) at the booting stage resulted in higher grain yield, nevertheless, cultivar, water, and nitrogen revealed different trends for some of the grain quality attributes i.e., brown rice rate, milled rice rate, head milled rice rate, protein content, and amylose content as well as nutrient uptake and use efficiencies in the double rice production system. Basmati had higher nitrogen harvest index (NHI) (18.28-20.23%) and P harvest index (PHI) (3.95-12.42%) but lower physiological P use efficiency for biomass (PPUEB) (7.66-23.66%) and physiological K use efficiency for biomass (PKUEB) (2.53-7.10%) than Nongxiang 18 in both seasons. Furthermore, the grain number per panicle, biomass yield, grain P uptake, and the whole plant P uptake were significantly related to the grain yield of fragrant rice. In both seasons, the interaction of water and nitrogen (W×N) had a significant effect on panicle number, grain quality attributes, and N, P uptake of straw, as well as the physiological N, P use efficiency for grain and the physiological N, K use efficiency for biomass. Overall, results suggest that moderate nitrogen and irrigation input at booting stage could feasible to improve the productivity and quality of double rice production system with improved nutrient use efficiency under agro-climatic conditions of South China.